Kerja Sama Internasional Indonesia dengan Korea Selatan dalam Pembuatan Pesawat Tempur KFX/IFX - Yohanes Purwanto (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2022)
The author focuses on the cooperation between Indonesia and South Korea which has existed since the opening of diplomatic relations in 1973. Until now, cooperation between Indonesia and South Korea is still ongoing, one of which is in the field of defense and security, namely by making KFX / IFX fighter aircraft. In a partnership, there are mutually agreed goals and objectives to achieve fair benefits. The purpose of the author is to analyze and find out the extent of cooperation between Indonesia and South Korea in the development of the KFX / IFX fighter aircraft. The author uses a qualitative method, so the author will discuss the history of cooperation in the manufacture of fighter aircraft, the manufacturing mechanism and the cost of making the KFX / IFX fighter aircraft, the purpose or motive for holding cooperation in the manufacture of a fighter aircraft that has the name KFX / IFX.